Hubungan Pola Asuh Orangtua Dengan Tingkat Kemandirian Secara Fisik Pada Anak Usia 4-6 Tahun Prasekolah di Tk GMIM Eben Haezar Kaaten - Eduard Jeconya Lengkong (Peneliti.net, 2022)
Independence is an individual's ability to manage himself and not depend on parents. The growth and development of the child's personality, especially independence, is influenced by the parenting style applied in the family. Appropriate parenting will increase children's independence and vice versa. The purpose of this study was to analyze the relationship between parenting style and the level of physical independence of children at preschool age (4-6 years) at GMIM Eben Haezar Kaaten Kindergarten. This type of research is Correlational Analytical, with a Cross Sectional approach. The population in this study were 25 student respondents at GMIM Eben Haezar Kaaten Kindergarten. The sampling technique used is Total Sampling. Methods of data collection using a questionnaire. The statistical test used in this study is Chi Square with α 0.05. The results of this study show that the level of physical independence is in the less independent category (64%) with permissive parenting (48%) and authoritarian parenting (16%). Chi Square analysis results obtained ρ value = 0.000 <α = 0.05, meaning that there is a relationship between parenting and the level of physical independence of children at preschool age (4-6 years) at GMIM Eben Haezar Kaaten Kindergarten with a closeness relationship of 0.707, which means a close relationship categorized as strong. From the results of research, parents are able to apply proper parenting to their children so that they can increase physical independence in children.